Cladonia rangiferina F. H. Wigg - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
3.3. Proposed polyketide synthesis in Cladonia rangiferina A pervious study (Elshobary et al., 2016) showed that CrPKS1 and CrPKS16 may be genes that encode non-reducing enzymes and CrPKS3 may encode a reducing enzyme. Furthermore, CrPKS1 was most closely related to the putative PKS from Pyrenophora tritici-repentis (Diedicke) Drechsler and Macrophomina phaseolina (Tassi) Goidanich (both with maximum identity of 78 and 79%, respectively), which were responsible for production of 6-methylsalicylic acid synthase. The 6-methylsalicylic acid is considered the first cyclic compound in the polyketide pathway and a common precursor for the cyclic polyketide compounds (Legaz et al., 2011). Alternatively, the C. grayi PKS1 ( CgPKS1 ) (similarity with CrPKS1 was 99% identity) was shown to fall within a phylogenetic clade that had a methyltransferase domain (Armaleo et al., 2011) suggesting it may produce the first cyclic compound (methyl-3-orsellinate) in the atranorin and fumarprotocetraric acid pathway (Fig. 4). Accordingly, CrPKS1 is expected to be highly expressed in the thallus outer layer where the acetate/malonate and cyclisation presumably occur after transportation of algal sugars. CrPKS16 was most closely related to the putative PKS from C. grayi ( CgPKS16 maximum identity of 100%) which was hypothesized to be responsible for the synthesis and linking of two cyclic compounds ( Methyl-3-orsellinate and sphaerophorolcarboxylic acid) to produce the grayanic acid precursor (4-O-demethylsphaerophorin; Fig. 5A) (Armaleo et al., 2011). Both 4-O-demethylsphaerophorin and atranorin are similar depsides except in the side chain at C 16 and the methylated carboxyl group (Fig. 5). Accordingly, CrPKS16 may be involved in the linkage of two cyclic compounds (Methyl-3-orsellinate and Haemmatomoyl alcohol) to form atranorin (Fig. 5B). CrPKS16 was expressed in both the outer and inner thallus tissue, which was consistent with the TLC data showing atranorin in both layers. However, the transformation of depsides to depsidones ...